2017
DOI: 10.21608/jppp.2017.46358
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Some Natural Substances for Control the Greater Wax Moth Galleria mellonella l. (Lepidoptera: Pyralidae)

Abstract: The present work studied the effect of some natural substances (Egyptian and Chinese propolis ethanolic extractcinnamon-clove-peppermint ethanolic extract) against the 4 th larval instar of G. mellonella. The experiments in this study were conducted in the experimental laboratory of Biology Department, Faculty of Science, Taibah University. Potential activities of active materials on mortality percent and duration of greater wax moth at four concentrations (0.5, 1.0, 2.0 and 4.0 % w/w) were studied, and it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…According to Ayman & Atef (2007), methyl salicylate, formic acid, clove oil, acetic acid and bacillus oil have high mortality. Fawzy et al (2017), investigated the effects of propolis, cinnamon, clove, and peppermint ethanolic extracts on the 4th larval instar of the Greater wax moth and found that peppermint extract was the most effective and propolis extract had no effect. According to Swamy et al (2006), mahua oil (63%), neem oil (62%), and pongamia oil (56%) cause a reduction in the Greater wax moth larvae populations.…”
Section: Discussionmentioning
confidence: 99%
“…According to Ayman & Atef (2007), methyl salicylate, formic acid, clove oil, acetic acid and bacillus oil have high mortality. Fawzy et al (2017), investigated the effects of propolis, cinnamon, clove, and peppermint ethanolic extracts on the 4th larval instar of the Greater wax moth and found that peppermint extract was the most effective and propolis extract had no effect. According to Swamy et al (2006), mahua oil (63%), neem oil (62%), and pongamia oil (56%) cause a reduction in the Greater wax moth larvae populations.…”
Section: Discussionmentioning
confidence: 99%
“…Pesticides extended by applied lead to natural enemies' destruction and also, destruction of the role of honey bees as pollinators. Natural plant products are an excellent alternative to pesticides as a tool decreasing the side effects on human health and the environment balance (Koul et al, 2008 andFawzy et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Bee products including bee venom; which is composed of active molecules and propolis; which is a resin composed of more than 300 components have shown a wide range of biological activities (Robertson, 1990;Wehbe et al, 2019;Przybyłek & Karpiński, 2019;Anjum et al, 2019). For insecticidal activities; Propolis showed toxicity against larval stages of the lesser wax moth (Achroia grisella) (Ararso & Legesse, 2016) and the Greater Wax Moth (Galleria mellonella) (Fawzy et al, 2017). Bee venom showed toxicity against eggs and larvae of Achroia grisella (Mahgoub et al, 2018) and larvae of the black soldier fly (Hermetia illucens) (Nassar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%